Alfvén wave characteristics of equatorial plasma irregularities in the ionosphere derived from CHAMP observations - Lühr, Hermann; Park, Jaeheung; Xiong, Chao; Rauberg, Jan (Frontiers in Physics, 2014)
We report magnetic field observations of the components transverse to the main field in the frequency range 1–25 Hz from times of equatorial plasma irregularity crossings. These field variations are interpreted as Alfvénic signatures accompanying intermediate-scale (150 m–4 km) plasma density depletions. Data utilized are the high-resolution CHAMP magnetic field measurements sampled at 50 Hz along the north-south satellite track. The recorded signals do not reflect the temporal variation but the spatial distribution of Alfvénic signatures. This is the first comprehensive study of Alfvénic signatures related to equatorial plasma bubbles that covers the whole solar cycle from 2000 to 2010. A detailed picture of the wave characteristics can be drawn due to the large number (almost 9000) of events considered. Some important findings are: Alfvénic features are a common feature of intermediate-scale plasma structures. The zonal and meridional magnetic components are generally well correlated suggesting skewed current sheets. The sheets have an orientation that is on average deflect by about 32° away from magnetic east toward upward or downward depending on the hemisphere. We have estimated the Poynting flux flowing into the E region. Typical values are distributed over the range 10−8–10−6 W/m2. Large Poynting fluxes are related to steep spectra of the Alfvénic signal, which imply passages through regularly varying electron density structures. No dependence of the Poynting flux level on solar activity has been found. But below a certain solar flux value (F10.7 < 100 sfu) practically no events are detected. There is a clear tendency that large Poynting flux events occur preferably at early hours after sunset (e.g., 20:00 local time). Toward later times the occurrence peak shifts successively toward lower energy levels. Finally we compare our observations with the recently published results of the high-resolution 3-D model simulations by Dao et al. [1].